2011
DOI: 10.1080/01431161.2011.596849
|View full text |Cite
|
Sign up to set email alerts
|

The impact of satellite-derived wind data assimilation on track, intensity and structure of tropical cyclones over the North Indian Ocean

Abstract: In the present satellite era, remote-sensing data are more useful to improve the initial condition of the model and hence the forecast of tropical cyclones (TCs) when they are in the deep oceans, where conventional observations are unavailable. In this study, an attempt is made to assess the impact of remotely sensed satellite-derived winds on initialization and simulation of TCs over the North Indian Ocean (NIO). For this purpose, four TCs, namely, 'Nargis', 'Gonu', 'Sidr' and 'KhaiMuk', are considered, with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
34
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 78 publications
(34 citation statements)
references
References 22 publications
0
34
0
Order By: Relevance
“…The application of such mesoscale models for TC forecasting over the NIO is a recent development. Osuri et al (2012a) demonstrated the promising ability of the ARW model for realtime prediction of TC track and intensity over the NIO during the 2008 season. This study also demonstrated that the performance of the ARW model was reasonably good in comparison with other global models.…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…The application of such mesoscale models for TC forecasting over the NIO is a recent development. Osuri et al (2012a) demonstrated the promising ability of the ARW model for realtime prediction of TC track and intensity over the NIO during the 2008 season. This study also demonstrated that the performance of the ARW model was reasonably good in comparison with other global models.…”
Section: Introductionmentioning
confidence: 96%
“…The other core version, the Nonhydrostatic Mesoscale Model (NMM), was developed at the Environmental Modeling Center of the National Centers for Environmental Prediction (NCEP). Over the Indian monsoon region, and indeed globally, the ARW model is being widely used for the simulation of a variety of weather events, such as heavy rainfall (Niyogi et al 2006;Routray et al 2010;Dodla and Ratna 2010;Hong and Lee 2009) and TCs (Osuri et al 2012a;Pattanaik and Rama Rao 2009;Davis et al 2008). The ARW model has been used for real-time TC forecasting since 2007.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of data assimilation on simulation of TCs over the NIO has been studied by several authors in the last decade (e.g. Singh et al, 2008Singh et al, , 2011Singh et al, , 2012aXiao et al, 2009;Krishna et al, 2010Krishna et al, , 2012Srinivas et al, 2010;Prashant et al, 2012;among others). However, most of these were individual case studies using various model configurations and with significant differences in the results due to the use of various data sources (satellite, radar, conventional, etc.)…”
Section: M Greeshma Et Al: Impact Of Local Data Assimilation On mentioning
confidence: 99%
“…Several model performance evaluation studies have been conducted for TC predictions in recent times (e.g. Prasad and Rama Rao, 2006;Davis et al, 2008;McNoldy et al, 2010;Yeh et al, 2012;Zhang et al, 2011;Srinivas et al, 2013;Krishna et al, 2012 among others) over different regions. In the USA, the Geophysical Fluid Dynamics Laboratory (GFDL) hurricane model and the Hurricane Weather Research and Forecasting (HWRF) model (Tallapragada et al, 2014) are widely used for operational hurricane predictions.…”
mentioning
confidence: 99%
“…The quality of initial conditions can be improved with the mesoscale data assimilation of high dense observations. Several previous studies have demonstrated that the assimilation of sea surface and upper air satellite-derived winds near and around the centre of the storm can substantially improve the initial analyses of TCs and hence the prediction of track, intensity and structure (Velden et al 1998, Chen 2007, Pu et al 2008, Osuri et al 2012b). …”
Section: Introductionmentioning
confidence: 99%